Defensive Strategies of Central Asian Republics: From Bipolarity to Multipolarity - Zahid Yaseen; Muhammad Muzaffar; Khadija Shahbaz, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
This qualitative study analyzes the world moves from a bipolar to a complex multipolar system, the importance of the Central Asian Region for all countries i.e., Russia, China, US, India, Iran, Turkey and Pakistan, geo-political and geo-strategic threats in a critical region of Central Asia. The regional powers including Russia and China dominate the US through the region; all these countries benefit from natural resources in this region. The result of this study shows that all countries especially developed states play an important role in this region to achieve their economic objective, US, China, and Russia hold proxy wars in this region due to communist and capitalist divisions. This study recommends Russia and China both have significant clout in Central Asia. Pakistan must establish friendly ties with these Central Asian and communist countries to get economic benefits. Pakistan should not be overly reliant on the Western bloc. States should maintain amicable ties with neighboring states.